Antioxidant capacities and anthocyanin characteristics of the black–red wild berries obtained in Northeast China. (1st August 2016) - Feng, Chengyong; Su, Shang; Wang, Lijin; Wu, Jie; Tang, Zhongqiu; Xu, Yanjun; Shu, Qingyan; Wang, Liangsheng
Highlights: Anthocyanins in 8 berry species from Northeast China were firstly reported. Four kinds of anthocyanins were firstly detected in Ribes rubrum . All black–red berries were of great potential for daily cyanidin consumption. Black berries were of higher TACs, TPCs and antioxidant capacities than red ones. Padus maackii and Padus avium exhibited significant higher TACs over others. Abstract: Various edible berries widely accessible in nature in Northeast China are poorly exploited. The compositions and contents of anthocyanins in black ( Padus maackii, Padus avium, Lonicera caerulea, and Ribes nigrum ) and red ( Ribes rubrum, Sambucus williamsii, Rubus idaeus, and Ribes procumbens ) wild berries in Northeast China were firstly characterized by HPLC–DAD/ESI-MS 2 . Twenty-three anthocyanins were detected and identified. Cyanidin glycosides were dominant in both berries. Six anthocyanins were reported for the first time in P . avium, R . rubrum, and Sambucus . Total anthocyanin content (TAC) ranged from 10 mg/100 g fresh weight (FW) ( R . procumbens ) to 1058 mg/100 g FW ( P . maackii ) among berries. The TACs and antioxidant activities assessed by DPPH and FRAP assays were much higher in black than in red berries. Black–red berries, especially P . maackii and P . avium, can be used in developing functional foods and in improving breeding programs.